(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article provides information on types of mental retardation in children and methods of prevention. Mentally retarded refers to a steady decline in mental, first of all, intellectual development as a result of organic damage to the brain. Mentally retarded children will not be able to master the program of general education schools. Children with severe mental retardation cannot acquire knowledge and skills at school.